Highly selective direct azidation of alcohols over a heterogeneous povidone-phosphotungstic solid acid catalyst - Kamble, Sumit; More, Sagar; Rode, Chandrashekhar V. (New Journal of Chemistry, 2016)
A simple protocol for the selective azidation of alcohols is developed using a solid acid hybrid of a povidone and phosphotungstic acid (PVP-PWA) using azidotrimethylsilane as an azide source at room temperature. In a broad substrate scope, various activated as well as unactivated benzylic and diphenyl alcohols were treated smoothly with TMS-N-3 to selectively produce only azide products with excellent yields in a very short reaction time of 2 h. FT-IR confirmed the stability of the catalyst with retention of the Keggins structure after the reaction. Recycling experiments demonstrated the reusability of the PVP PWA (3:1) several times without losing its original activity.